Reflections on Reflection The Student Teaching Seminar - Grippin, Pauline C. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
This paper reports on a preliminary look at the student teaching seminar as a vehicle for encouraging reflective thinking about teaching and learning. The seminar group was composed of 32 undergraduate and graduate students, student teachers in the secondary school disciplines. A preliminary self-analysis essay written by the student teachers addressed the issues of career choice, purposes of education, student-teacher relationship, and perceived strengths and weaknesses. The students attended a weekly cross-discipline seminar in which the reflective teacher model was explained and endorsed. Students were required to reflect upon readings, structured observations of practicing teachers, and their own planning for teaching. Discussions of teaching strategies, goals and objectives, and contextual issues were held concurrently with field experiences. In the final class period, students responded anonymously to a survey on their perceptions of change in their ideas and goals as a function of the student teaching experience and the seminar experience. An analysis of the results of the study indicated that the student teaching seminar has potential as a vehicle for educational change via the encouragement of reflective practice. Results are displayed in seven tables; the two essay-type questionnaires are included. (JD)
ERIC Note: Paper presented at the Annual Conference of the Eastern Educational Research Association (Clearwater, FL, February 15, 1990).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cognitive Style; Conceptual Tempo; Critical Thinking; Higher Education; Preservice Teacher Education; Program Effectiveness; Reflective Teaching; Secondary Education; Seminars; Student Teacher Attitudes; Student Teaching; Speeches/Meeting Papers; Reports, Research